Analysis of the Meaning Components of the Lyrics of the Song "Selalu Ada di Nadimu": A Semantic Study: - Rizal, Muhammad (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the components of meaning contained in the lyrics of the song “Selalu Ada di Nadimu” (Jumbo Film Soundtrack) through a component analysis approach. The study used a qualitative descriptive method, with data consisting of key words in the lyrics that play a significant role in constructing the song’s emotional and relational messages. Data were collected using reading and note-taking techniques, then analyzed using a combination of direct element analysis and semantic analysis techniques to identify shared, distinctive, and additional components of meaning. The results show that the words “singing,” “prayer,” and “word” share similarities as forms of affective expression, but differ in aesthetic aspects and spiritual purpose. The words “smile,” “happy,” and “love” share the same emotional meaning field, but differ in visibility, depth of affection, and interpersonal relationships. The words “storm” and “wind” depict differences in intensity and threat in metaphors of life’s challenges. Overall, this study confirms that song lyrics utilize metaphorical and emotional diction with a layered structure of meaning components, allowing for a more profound message of affection, steadfastness, and emotional support.